Muslims and the State in Britain, France, and Germany: By Joel S. Fetzer and J. Christopher Soper (Cambridge: Cambridge University Press, 2003. 208 pages.) (American Journal of Islam and Society, 2005)
The expanding Muslim communities in Western Europe have become asource of consternation in European capitals. Central to the issue ofEurope’s growing Muslim population is how far the secular state is willingto accommodate religious practices deemed to be antithetical to “European”values. Fetzer and Soper’s timely comparative study effectively addressesthe issue’s historical foundations as well as clearly explains the EuropeanMuslims’ disparate political responses.The authors’ central focus is how three core European states haveaccommodated the needs of Muslims flooding their borders since the 1960s.Exploring Europe’s surprisingly disjointed response to Muslim immigrationproves to be both theoretically interesting and an invaluable exercise indebating what options are available to elected governments that are beingincreasingly pressured by right-wing activism when it comes to accommodatethe practice of Islam in Europe.The questions raised in the book’s six chapters, three of which are dedicatedto the countries in question and the others to presenting the data collectedvia the authors’ surveys, should prove helpful to larger discussions inEuropean studies about what the contemporary dilemmas facing Germany,Britain, and France are in the context of the so-called war on terrorism.While most studies on Islam in Europe, particularly migration and genderstudies, focus on how Muslims mobilize their socioeconomic resources,Fetzer and Soper contend that developing a public policy on Muslim religious(and political) rights is actually mediated in significant ways by thedifferent institutional church/state patterns within each country.This move away from the assumption that Muslims, if organized in theright way, could expect certain institutional concessions in “democraticEurope” proves to be a helpful intervention into a sometimes doctrinally ...